A pH/ROS dual-responsive and targeting nanotherapy for vascular inflammatory diseases. (February 2020) - Zhang, Runjun; Liu, Renfeng; Liu, Chao; Pan, Lina; Qi, Yuantong; Cheng, Juan; Guo, Jiawei; Jia, Yi; Ding, Jun; Zhang, Jianxiang; Hu, Houyuan
Abstract: Cardiovascular diseases (CVDs) remain the leading cause of morbidity and mortality worldwide. Vascular inflammation is closely related to the pathogenesis of a diverse group of CVDs. Currently, it remains a great challenge to achieve site-specific delivery and controlled release of therapeutics at vascular inflammatory sites. Herein we hypothesize that active targeting nanoparticles (NPs) simultaneously responsive to low pH and high levels of reactive oxygen species (ROS) can serve as an effective nanoplatform for precision delivery of therapeutic cargoes to the sites of vascular inflammation, in view of acidosis and oxidative stress at inflamed sites. The pH/ROS dual-responsive NPs were constructed by combination of a pH-sensitive material (ACD) and an oxidation-responsive material (OCD) that can be facilely synthesized by chemical functionalization of β-cyclodextrin, a cyclic oligosaccharide. Simply by regulating the weight ratio of ACD and OCD, the pH/ROS responsive capacity can be easily modulated, affording NPs with varied hydrolysis profiles under inflammatory microenvironment. Using rapamycin (RAP) as a candidate drug, we first demonstrated in vitro therapeutic advantages of RAP-containing NPs with optimal dual-responsive capability, i.e. RAP/AOCD NP, and a non-responsive nanotherapy (RAP/PLGA NP) and two single-responsive nanotherapies (RAP/ACD NP and RAP/OCD NP) were used as controls. In an animal model of vascular inflammation in rats subjected to balloon injury in carotid arteries, AOCD NP could accumulate at the diseased site after intravenous ( i.v. ) injection. Consistently, i. v. treatment with RAP/AOCD NP more effectively inhibited neointimal hyperplasia in rats with induced arterial injuries, compared to RAP/PLGA NP, RAP/ACD NP, and RAP/OCD NP. By surface decoration of AOCD NP with a peptide (KLWVLPKGGGC) targeting type IV collagen (Col-IV), the obtained Col-IV targeting, dual-responsive nanocarrier TAOCD NP showed dramatically increased accumulation at injured carotid arteries. Furthermore, RAP/TAOCD NP exhibited significantly potentiated in vivo efficacy in comparison to the passive targeting nanotherapy RAP/AOCD NP. Importantly, in vitro cell culture experiments and in vivo animal studies in both mice and rats revealed good safety for AOCD NP and RAP/AOCD NP, even after long-term treatment via i. v. injection. Consequently, our results demonstrated that the newly developed Col-IV targeting, pH/ROS dual-responsive NPs may serve as an effective and safe nanovehicle for precision therapy of arterial restenosis and other vascular inflammatory diseases.